2023
DOI: 10.1186/s11556-023-00319-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based manual dexterity training on cognitive function among older adults: a randomized controlled trial

Abstract: Background The relationship between manual dexterity and cognitive function among older adults is well known; however, few studies have focused on manual dexterity training that confirms cognitive load of training in older adults through functional near-infrared spectroscopy (fNIRS) and verifies the effect of training. This study examined the effects of home-based manual dexterity training on cognitive function in older adults using a digital trail-making peg test device combining two conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…One factor that may have contributed to the increase in PFC activity is the strong association between hand and finger movements and the PFC. Previous studies in older adults demonstrated that hand and finger manipulation exercises increase blood flow to the PFC and improve executive function 46 . Regarding the improvement in cerebral blood flow to the PFC, the results of Event F in the present study are consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor that may have contributed to the increase in PFC activity is the strong association between hand and finger movements and the PFC. Previous studies in older adults demonstrated that hand and finger manipulation exercises increase blood flow to the PFC and improve executive function 46 . Regarding the improvement in cerebral blood flow to the PFC, the results of Event F in the present study are consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Light-intensity exercises were selected from a list of commonly practiced static and dynamic stretching exercises 50 , 51 . In addition, as previous studies have shown that hand and balance exercises activate the prefrontal cortex 46 , 48 , 52 , these exercises were also included. All events were performed while seated, except for the standing balance exercise, to minimize body movement noise.…”
Section: Methodsmentioning
confidence: 99%
“…Relational and hyperactivity scores were negatively correlated with social cognition and facial recognition of affect, indicating the importance of social cognition and theory of mind in relational life and social conduct [24]. High scores of social conduct, hyperactivity and negative impact of behavioural di culties were negatively associated with digital dexterity performance, suggesting possible prefrontal impairment in hyperactivity and social conduct disorder [25].…”
Section: Cognitive Performance and Behavioural Characteristicsmentioning
confidence: 98%
“…Finger-tapping performance has been shown to decline among older individuals as the brain and cognitive functions deteriorate (Suzumura et al, 2021 ; Sugioka et al, 2022 ). In addition, finger tapping is effective in improving the activities of daily living (ADL) (Liu et al, 2018 ), and hand training may improve dexterity and executive function and, over the long term, cognitive function (Seol et al, 2023 ). In general, older adults have been shown to engage a broader range of brain regions for motor control than younger adults, particularly prefrontal regions and basal ganglia networks, and motor control becomes more dependent on cognition and the prefrontal cortex (PFC) with aging (Seidler et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%